Mindfulness and its relationship to Empathy and Prosocial Behavior among Yemeni students in China - Al-Dbyani, Amer Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the level of mindfulness, and the relationship between mindfulness, empathy, and pro-social behavior among a sample of Yemeni students at Chinese Universities. The study sample consisted of (509) male and female students who were enrolled in the second semester of 2019-2020. The results showed a low level of mindfulness and empathy, and a medium level of pro-social behavior, while the relationship between all the five-facet mindfulness and both empathy and prosocial behavior were significant and positive. The results also showed statistically significant differences in the level of mindfulness to gender in favor of males. In addition, the study found as well, differences in the level of empathy to gender in favor of females, while there are no significant differences in the level of pro-social behavior. The study concluded with a number of recommendations, the most important of which are: Implementing training programs to provide Yemeni students in China with mental alertness skills.